2015
DOI: 10.1177/194008291500800316
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perception of Urban and Rural Environmental Protection Areas in Pernambuco, Brazil

Abstract: This research assessed the relationship between students' perceptions and socioeconomic factors in urban and rural communities surrounding Atlantic rainforest protection areas in Pernambuco, Brazil. We tested whether the utilitarian concept of forests has a determining role in the student community's perception of protected areas. The study was conducted in eight schools in communities surrounding three protected areas, through questionnaires for 410 middle and High school students. The majority of students hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
2
6
0
3
Order By: Relevance
“…The research findings confirm the results of previous studies (e.g. [19]) that the majority of school students do not possess sufficient knowledge about the meaning of protected areas in nature. Some confuse them with city parks and other areas that are clearly not established for the purpose of nature conservation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The research findings confirm the results of previous studies (e.g. [19]) that the majority of school students do not possess sufficient knowledge about the meaning of protected areas in nature. Some confuse them with city parks and other areas that are clearly not established for the purpose of nature conservation.…”
Section: Discussionsupporting
confidence: 89%
“…Ferreira [18] stated that the environmental integrity of many urban protected areas in developing countries is at risk and sees the opportunity in reaching out to people living close to them to spread the conservation message. Bent-Silva et al [19] reported that approximately 60% of Brazilian middle and high school students from schools in communities near protected areas did not answer the question regarding the meaning of protected areas.…”
Section: Protected Areasmentioning
confidence: 99%
“…The positive influence of age on the knowledge of medicinal plants that we detected in our research was also recorded in several studies [10, 11, 14, 36]. Such a finding was expected, as older people are likely to have more time to accumulate life-long experiences.…”
Section: Discussionsupporting
confidence: 88%
“…Welle & Kating (2018) acreditam que as políticas ambientais dos Estados Unidos da América abrem precedentes de prejuízos irreversíveis à natureza, provavelmente não sendo essa a principal motivação para estudos da causa ambiental, porém é um bom pretexto. O Brasil vem em segundo lugar no número de publicações, sendo um dos países possuidores de maior biodiversidade do mundo, este também é um país de grande sociobiodiversidade, endente-las e protege-las seria a maior motivação em estuda-las na perspectiva da percepção ambiental, sendo uma temática amplamente discutida na criação de políticas públicas, elaboração de planos com práticas voltadas para a educação ambiental, gestão ambiental e valorização do conhecimento popular tradicional, conforme apresentado e defendido por Rodrigues et al (2012), Pellier et al (2014), Bener et al (2014), Bento-Silva et al (2015, Dictoro et al (2017) e Oliveira et al (2017). Isto leva a reafirmar a multi, inter e transdisciplinaridade que envolve as pesquisas relacionadas ao tema, fato também observado por Vasco & Zakrzevski (2010).…”
Section: Discussionunclassified